PRODUKSI TANAMAN JAGUNG (Zea mays L.) DENGAN PEMBERIAN PUPUK ORGANIK KITOSAN DAN PUPUK NITROGEN - Eltis Panca Ningsih; Imas Rohmawati; Dewi Hastuti; Mistar Mistar (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
The goal of this research was to determine the growth response and yield of corn plants (Zea mays L.) towards the application of chitosan organic fertilizer and nitrogen fertilizer. This research used randomized block design which consists of two factors. The first factor was the concentration of chitosan organic fertilizer whith four levels: 0 ppm/ plant, 10 ppm/ plant, 20 ppm/ plant, and 30 ppm/ plant. The second factor was the dose of nitrogen fertilizer with four levels 0 g/plant, 5 g/plant, 10 g/plant and 15 g/plant. There was 16 combinations of treatments. Each treatments was replicated three times to obtain 48 experimental units. Parameters observed were number of cobs per plant, number of seeds per plant and weight 100 seeds. The results of this research showed that application of chitosan fertilizer does not affect the yield of corn plants. Chitosan fertilization with a concentration of 10 ppm tends to show higher yields on the parameters of the number of cobs (2.25 cobs) and weight of 100 seeds (35.00 g). The application of nitrogen fertilizer affects the yield of corn plants. Nitrogen fertilization with a dose of 15 g/plant increased the number of cobs (2.83 cobs) and the number of seeds per plant (647.75 seeds) compared to the control treatment. There is no interaction between chitosan fertilizer and nitrogen fertilizer on corn yields.